A method to decompose spectral changes in Synechocystis PCC 6803 during light-induced state transitions - Alonso M. Acuña; Radek Kaňa; Michal Gwizdala; Joris J. Snellenburg; Pascal van Alphen; Bart van Oort; Diana Kirilovsky; Rienk van Grondelle; Ivo H. M. van Stokkum (Photosynthesis Research, 2016)

The rich sides of mountain summits – a pan‐European view on aspect preferences of alpine plants - Manuela Winkler; Andrea Lamprecht; Klaus Steinbauer; Karl Hülber; Jean‐Paul Theurillat; Frank Breiner; Philippe Choler; Siegrun Ertl; Alba Gutiérrez Girón; Graziano Rossi; Pascal Vittoz; Maia Akhalkatsi; et al. (Journal of Biogeography, 2016)
Aim In the alpine life zone, plant diversity is strongly determined by local topography and microclimate. We assessed the extent to which aspect and its relatedness to temperature affect plant species diversity, and the colonization and disappearance of species on alpine summits on a pan‐European scale. Location Mountain summits in Europe's alpine life zone. Methods Vascular plant species and their percentage cover were recorded in permanent plots in each cardinal direction on 123 summits in 32 regions across Europe. For a subset from 17 regions, resurvey data and 6‐year soil temperature series were available. Differences in temperature sum and Shannon index as well as species richness, colonization and disappearance of species among cardinal directions were analysed using linear mixed‐effects and generalised mixed‐effects models, respectively. Results Temperature sums were higher in east‐ and south‐facing aspects than in the north‐facing ones, while the west‐facing ones were intermediate; differences were smallest in northern Europe. The patterns of temperature sums among aspects were consistent among years. In temperate regions, thermal differences were reflected by plant diversity, whereas this relationship was weaker or absent on Mediterranean and boreal mountains. Colonization of species was positively related to temperature on Mediterranean and temperate mountains, whereas disappearance of species was not related to temperature. Main conclusions Thermal differences caused by solar radiation determine plant species diversity on temperate mountains. Advantages for plants on eastern slopes may result from the combined effects of a longer diurnal period of radiation due to convection cloud effects in the afternoon and the sheltered position against the prevailing westerly winds. In northern Europe, long summer days and low sun angles can even out differences among aspects. On Mediterranean summits, summer drought may limit species numbers on the warmer slopes. Warmer aspects support a higher number of colonization events. Hence, aspect can be a principal determinant of the pace of climate‐induced migration processes.